Work Discipline and Financial Compensation Effect on Employees’ Performance in Library and Regional Archives of Ternate City - Nurlaila Nurlaila; Risdam Buamona (AIBPM Publisher, 2020)
This study aims to determine the work discipline and financial compensation effect on employee performance, partially and simultaneously, as well as the dominant variables that affect employee performance. Respondents used in this study were 40 people. The method of analysis uses multiple linear regression and to test the hypothesis using SPSS as a statistical test tool. The results showed that partially the work discipline variable (X1) and compensation variable (X2) had a positive and significant effect on employee performance, and simultaneously work discipline and financial compensation had a positive and significant effect on the Ternate City Regional Library and Archives employees’ performance.